Characterization of the tumor immune-microenvironment of lung adenocarcinoma associated with usual interstitial pneumonia. (December 2018) - Ueda, Takuya; Aokage, Keiju; Mimaki, Sachiyo; Tane, Kenta; Miyoshi, Tomohiro; Sugano, Masato; Kojima, Motohiro; Fujii, Satoshi; Kuwata, Takeshi; Ochiai, Atsushi; Kusumoto, Masahiko; Suzuki, Kenji; et al.
Highlights: UIP-ADC patients had worse prognosis than non-UIP ADC patients. UIP-ADC patients exhibited reduced levels of CD8 + TILs. The CD8 + /Foxp3 + T cell ratio was significantly reduced in UIP-ADC. The tumor microenvironment of UIP-ADC acquires an immunosuppressive state. Abstract: Background: Lung cancer with usual interstitial pneumonia (UIP) pattern is a disease with poor prognosis. This study aimed to characterize the tumor microenvironment of lung adenocarcinoma associated with UIP (UIP-ADC). Methods: A total of 1341 consecutive patients with ADC who had undergone complete surgical resection were enrolled in this study, and the clinicopathological features of UIP-ADC were examined. Further, we selected 17 cases of UIP-ADC and non-UIP ADC each (adjusted for age, smoking status, pathological stage, and invasive size of lesion) for immunohistochemical analysis, and the biological differences between UIP-ADC and non-UIP ADC groups were analyzed. Results: UIP-ADC was detected in 18 patients (1.3%). Patients with UIP-ADC had shorter cancer-specific survival (CSS) (5 yrs CSS; UIP-ADC 52.9% vs non-UIP ADC 81.8%, p < 0.01). Evaluation of tumor-infiltrating lymphocytes (TILs) in cancer stroma showed that the number of CD8 + TILs in UIP-ADC group was significantly lower than that in the non-UIP ADC group (median number 91 vs 121, p < 0.01). In contrast, levels of Foxp3 + TILs were not significantly different between the two groups. The CD8 + /Foxp3 + T cell ratio was significantly lower in UIP-ADC than in the non-UIP ADC population (1.9 vs 2.7, p < 0.01). Additionally, among UIP-ADC patients, the CD8 + /Foxp3 + T cell ratio was significantly higher in the non-cancerous UIP lesions than in the cancer stroma from the same patient (2.4 vs 1.7, p < 0.01). Conclusion: In the current study, we have demonstrated that the tumor microenvironment of UIP-ADC acquires an immunosuppressive state, and this could be one of the possible explanations for poor prognosis of this disease.